Strategi Sosialisasi Politik di DPD PDIP Provinsi Kalimantan Tengah dalam Pemilu 2024 dan Pilkada 2029 - Andes Cintia Ningrum (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The political socialization strategy of PDIP’s Regional Leadership Council in Central Kalimantan for the 2024 Election and 2029 Regional Election was examined through qualitative methods, including in-depth interviews with key party figures. Findings highlight three core strategies: grassroots cadre and sympathizer mobilization, digital media utilization for political communication, and involvement of local leaders and communities. Social media platforms like Instagram and WhatsApp effectively targeted urban youth, while face-to-face community engagement dominated rural areas. The party emphasized message consistency through structured coordination and ongoing political education. These strategies reflect PDIP’s adaptability to socio-cultural and technological contexts, fostering emotional bonds with constituents